Polyglycolic acid resin composition as well as preparation method and application thereof

By adding polyglycolic acid graft copolymers with special side chain groups to polyglycolic acid and aliphatic dibasic acid-aromatic dibasic acid-diol copolyesters, the shortcomings of existing polyglycolic acid compositions in terms of aging stability and thermal stability are solved, and the strength, toughness and heat sealing performance are improved, meeting the application needs in the packaging field.

CN119842187APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311332999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing polyglycolic acid compositions have shortcomings in aging stability and thermal stability, resulting in limited application in the packaging field.

Method used

By adding polyglycolic acid graft copolymer with special side chain groups to PGA and aliphatic dibasic acid-aromatic dibasic acid-diol copolyester, the compatibility of PGA and copolyester is enhanced, and the heat sealing performance and aging stability of the composition are improved.

Benefits of technology

The strength and toughness of the polyglycolic acid resin composition are synergistically improved, the heat sealing performance is excellent, and its aging stability is significantly improved, meeting the application needs in the packaging field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842187A_ABST
    Figure CN119842187A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and provides a polyglycolic acid resin composition as well as a preparation method and application thereof. The polyglycolic acid resin composition comprises polyglycolic acid, aliphatic dibasic acid-aromatic dibasic acid-dihydric alcohol copolyester, a polyglycolic acid grafted copolymer and a functional auxiliary agent. Wherein a structural unit with a side chain in a side chain of the polyglycolic acid grafted copolymer is a derivative of a monomeric compound containing at least one alpha, beta-unsaturated group. Due to the compatibilization effect of the polyglycolic acid grafted copolymer with a special structure, the polyglycolic acid film with synergistically improved mechanical strength and toughness is obtained, and the aging stability is more excellent. The invention provides an effective solution for preparing the degradable PGA film with long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a polyglycolic acid resin composition and a preparation method and application thereof. Background Art

[0002] Polyglycolic acid (PGA) has a wide range of practical applications in biomedical fields such as surgical sutures and artificial bones due to its excellent biocompatibility and rapid degradability. PGA is a linear semi-crystalline polyester polymer material with the least number of monomer carbons and the simplest structure. It has the mechanical properties of high crystallinity, high strength and high modulus. However, pure PGA has disadvantages such as poor toughness, easy aging and degradation, and poor heat sealing performance, which greatly limits its application in daily film bag products.

[0003] In order to solve the problem of poor mechanical toughness and poor processability of PGA, it is currently mainly melt-blended with flexible degradable polyesters such as poly (butylene adipate / terephthalate) to prepare the corresponding PGA modified blend. In order to solve the problem of easy degradation of PGA, Chinese patent CN114075378A proposes to add isocyanate compounds to PGA, and the concentration of terminal carboxyl groups is reduced by the reaction of isocyanate compound reactive groups with PGA end groups, thereby improving the aging stability of the PGA composition. In order to solve the problem of easy degradation of degradable polyesters during high-temperature processing, Chinese patent CN109575536A discloses a polyglycolic acid composition, which melt-blends PGA with PBAT, and increases its processing stability and service life by adding anti-hydrolysis agents, anti-oxygen agents and other additives. However, there are currently few technical reports on improving the heat sealing strength of PGA blend films. Due to the poor aging stability and thermal stability of the polyglycolic acid composition in the prior art, it is impossible to meet the actual application requirements, which limits the application scenarios of PGA in the packaging field. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a polyglycolic acid resin composition and a preparation method and application thereof. The present invention achieves enhanced compatibility of PGA with aliphatic dibasic acid-aromatic dibasic acid-diol copolyester by adding a polyglycolic acid graft copolymer having a special side chain group to PGA and aliphatic dibasic acid-aromatic dibasic acid-diol copolyester, and obtains a polyglycolic acid resin composition with synergistically improved strength and toughness and excellent heat sealing performance. At the same time, the introduction of a special side chain group can protect the ester bond degradation of PGA and significantly improve its aging stability.

[0005] One of the purposes of the present invention is to provide a polyglycolic acid resin composition, comprising: polyglycolic acid, polyglycolic acid graft copolymer, a mixture of aliphatic dibasic acid-aromatic dibasic acid-diol copolyester and / or a reaction product thereof, wherein the structural unit with a side chain in the polyglycolic acid graft copolymer is a derivative of a monomer compound containing at least one α, β-unsaturated group. The derivative can be a modified compound of a functional group in a monomer compound containing at least one α, β-unsaturated group, or an oligomer or other type of graft of the above monomer compound.

[0006] According to the present invention, in the polyglycolic acid resin composition:

[0007] The monomer compound containing at least one α,β-unsaturated group is selected from at least one of acrylic unsaturated monomers containing a cyclic structure, preferably at least one of cyclohexyl methacrylate, dicyclopentyl methacrylate, isobornene acrylate, benzyl acrylate, benzyl methacrylate, and glycidyl acrylate;

[0008] In the polyglycolic acid graft copolymer, the main chain structure accounts for 80-99% of the total mass of the copolymer, and the side chain structure accounts for 1-20% of the total mass of the copolymer; preferably, in the polyglycolic acid graft copolymer, the main chain structure accounts for 95-99% of the total mass of the copolymer, and the side chain structure accounts for 1-5% of the total mass of the copolymer;

[0009] The weight average molecular weight of the polyglycolic acid graft copolymer is 80,000 to 300,000 g / mol, preferably 110,000 to 160,000 g / mol;

[0010] The weight average molecular weight of the polyglycolic acid is 100,000 to 1,000,000 g / mol, and the molecular weight distribution index (PDI) is 1 to 5; preferably, the weight average molecular weight of the polyglycolic acid is 100,000 to 500,000 g / mol, and the molecular weight distribution index (PDI) is 1 to 3;

[0011] The intrinsic viscosity of the polyglycolic acid is 0.9 to 7 dl / g, preferably 1 to 5 dl / g;

[0012] The melt flow rate of the polyglycolic acid measured at 230° C. and 2.16 kg is 1 to 90 g / 10 min, preferably 1 to 50 g / 10 min;

[0013] The aliphatic dibasic acid-aromatic dibasic acid-diol copolyester is selected from at least one of polybutylene adipate terephthalate and polybutylene succinate terephthalate.

[0014] According to the present invention, the thermal decomposition temperature T of the polyglycolic acid resin composition for 5% weight loss is d(5%)>340℃, the average diameter of the dispersed phase of polyglycolic acid in the microstructure observed by scanning electron microscope is <400nm.

[0015] According to the present invention, in the polyglycolic acid resin composition:

[0016] Taking the total mass of the polyglycolic acid, the polyglycolic acid graft copolymer and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the polyglycolic acid accounts for 10-70%, the polyglycolic acid graft copolymer accounts for 1-20%, and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester accounts for 10-89%; preferably, taking the total mass of the polyglycolic acid, the polyglycolic acid graft copolymer and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the polyglycolic acid accounts for 20-60%, the polyglycolic acid graft copolymer accounts for 1-10%, and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester accounts for 30-79%.

[0017] According to the present invention, the polyglycolic acid resin composition further comprises a functional auxiliary agent, preferably, the functional auxiliary agent is selected from at least one of antioxidant A, chain extender, and opening agent. The antioxidant A, chain extender, and opening agent can all adopt the component compounds and dosages commonly used in the art. For example, the antioxidant A is selected from at least one of hindered phenols, hindered amines, phosphites, and thiols; the chain extender is selected from at least one of multifunctional compounds or grafts containing multiple epoxy groups or isocyanate groups, preferably at least one of diphenylmethane diisocyanate, dioxazoline, glycidyl methacrylate, and styrene-methyl methacrylate-maleic anhydride copolymer; the opening agent is selected from fatty acid amide compounds, preferably from oleic acid acyl esters. At least one of amine, erucic acid amide, and stearic acid amide; based on the total mass of the polyglycolic acid, polyglycolic acid graft copolymer and aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the functional additive is 0.1-15%, preferably 0.5-10%; wherein, when antioxidant A, chain extender, and opening agent are added according to actual needs, antioxidant A can be 0.1-1%, preferably 0.1-0.6%; chain extender can be 0.01-10%, preferably 0.01-5%; opening agent can be 0-8%, preferably 0-5%.

[0018] The second object of the present invention is to provide a method for preparing the above-mentioned polyglycolic acid resin composition, comprising: fully mixing the components including the polyglycolic acid, aliphatic dibasic acid-aromatic dibasic acid-diol copolyester, and polyglycolic acid graft copolymer, and obtaining the polyglycolic acid resin composition by melt blending and extrusion.

[0019] According to the present invention, in the method for preparing the polyglycolic acid resin composition:

[0020] Before mixing, the polyglycolic acid, aliphatic dibasic acid-aromatic dibasic acid-diol copolyester, and polyglycolic acid graft copolymer are dried, wherein the drying can be carried out using the drying equipment and drying conditions commonly used in the art, such as vacuum drying, hot air drying, etc. Preferably, the drying temperature is 10 to 80° C., preferably 10 to 40° C.; the water content of the polyglycolic acid after drying is less than 100 ppm, preferably less than 80 ppm;

[0021] The melt blending extrusion operation can be achieved by using a twin-screw extruder. Specifically, the melt blending extrusion conditions are: the melt blending extrusion temperature is 180-260°C, and the extruder speed is 10-500rpm; preferably, the melt blending extrusion temperature is 190-250°C, and the extruder speed is 100-250rpm;

[0022] After melt blending and extrusion, the obtained material can be cooled, granulated and packaged by conventional operations, wherein the cooling can be air cooling or water cooling.

[0023] According to the present invention, in the preparation method of the polyglycolic acid resin composition, a functional additive is further added during the mixing process, and the functional additive is selected from at least one of antioxidant A, a chain extender, and an opening agent. The antioxidant A, chain extender and opening agent can all adopt the component compounds and dosages commonly used in the art. For example, the antioxidant A is selected from at least one of hindered phenols, hindered amines, phosphites and thiols; the chain extender is selected from at least one of multifunctional compounds or grafts containing multiple epoxy groups or isocyanate groups, preferably at least one of diphenylmethane diisocyanate, dioxazoline, glycidyl methacrylate, and styrene-methyl methacrylate-maleic anhydride copolymer; the opening agent is selected from fatty acid amide compounds, preferably at least one of oleic acid amide, erucic acid amide, and stearic acid amide; based on the total mass of the polyglycolic acid, polyglycolic acid graft copolymer and aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the antioxidant A is 0.1-1%, preferably 0.1-0.6%; the chain extender is 0.01-10%, preferably 0.01-5%; the opening agent is 0-8%, preferably 0-5%.

[0024] According to the present invention, the polyglycolic acid graft copolymer is obtained by mixing polyglycolic acid and an acrylic unsaturated monomer containing a cyclic structure and subjecting the mixture to a grafting reaction under the action of an initiator. The grafting reaction is preferably carried out using a screw extruder, and more preferably, the screw extruder is a twin-screw extruder.

[0025] Specifically, in the grafting reaction of the polyglycolic acid graft copolymer:

[0026] The initiator is selected from organic peroxide initiators, preferably at least one selected from cumene hydroperoxide, tert-butylbenzene peroxide, dibenzoyl peroxide, and dicumyl peroxide;

[0027] Based on the total mass of the polyglycolic acid and the acrylic unsaturated monomer containing a cyclic structure as 100%, the acrylic unsaturated monomer is 0.1 to 5%, preferably 1 to 3%;

[0028] Based on the total mass of the polyglycolic acid and the acrylic unsaturated monomer containing a cyclic structure as 100%, the initiator is 0.01 to 1%, preferably 0.05 to 0.3%;

[0029] The temperature of the grafting reaction is 170 to 250°C, preferably 180 to 240°C;

[0030] Antioxidant B is optionally added during the mixing process, wherein the antioxidant B is selected from at least one of hindered phenols, hindered amines, phosphites, and thiols; based on the total mass of the polyglycolic acid and the acrylic unsaturated monomer containing a cyclic structure as 100%, the antioxidant B is 0.1-5%.

[0031] The third object of the present invention is to provide an application of the polyglycolic acid resin composition or the polyglycolic acid resin composition obtained by the above preparation method in the preparation of blown film, cast film, injection molded parts, and sheets. The application field is not particularly limited, including but not limited to applications in medical treatment, packaging, oil production, etc. More specifically, it can be applied to film bags, sheets, injection molded parts, straws, lunch boxes and other products.

[0032] According to the present invention, the heat sealing strength of the polyglycolic acid resin composition film is greater than 8N, and the elongation at break retention rate after xenon lamp aging for 100 hours is greater than or equal to 16%.

[0033] According to the present invention, the blown film and cast film can be processed into a film by using the equipment and operation process commonly used in the art to process the polyglycolic acid resin composition, and then cooled, shaped, stretched, and rolled into a film; the injection molded part can be processed by a commonly used injection molding machine and obtained by injection molding and demolding.

[0034] The polyglycolic acid (PGA) used in the present invention is also known as polyglycolic acid, which is a thermoplastic linear aliphatic polyester with the simplest structure. PGA can be prepared by methods such as glycolic acid melt polycondensation or glycolide ring-opening grafting, and is a typical high-crystallinity grafted product with a stable lattice, a high melting point, and advantages in mechanical strength. However, as an aliphatic polyester, the ester bond of the PGA main chain is easily hydrolyzed and aged to accelerate its own degradation, so its product stability is poor. At the same time, due to the fast crystallization rate of PGA, its film toughness is poor, and the poor blown film processability limits its application.

[0035] The present invention provides a polyglycolic acid resin composition and a preparation method and application thereof. After melt blending, extrusion, cooling and granulation of components such as polyglycolic acid, polyglycolic acid graft copolymer, aliphatic dibasic acid-aromatic dibasic acid-diol copolyester, a polyglycolic acid resin composition with stable processing performance is obtained. The advantage of the present invention is that the use of a polyglycolic acid graft copolymer with a specific structure can reduce the phase structure size of PGA in the blend and improve the compatibility between PGA and two degradable polyesters, aliphatic dibasic acid-aromatic dibasic acid-diol copolyester. At the same time, due to the non-polar cyclic structure side chain contained in the polyglycolic acid graft copolymer, strong steric hindrance protection is given to PGA, so that after the special structure graft copolymer is added to the composition, the polyglycolic acid resin composition can be given excellent ultraviolet aging stability. After 144 hours of ultraviolet aging, it still has high mechanical strength and elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] FIG. 1 is a cross-sectional SEM image of the polyglycolic acid resin composition particles of Comparative Example 1 (a) and the polyglycolic acid resin composition film of Comparative Example 1 in the MD direction (b).

[0037] FIG. 2 is a cross-sectional SEM image of the polyglycolic acid resin composition particles of Comparative Example 2 (a) and the polyglycolic acid resin composition film of Comparative Example 2 in the MD direction (b).

[0038] FIG. 3 is a cross-sectional SEM image of the polyglycolic acid resin composition particles of Example 1 (a) and the polyglycolic acid resin composition film of Example 2 in the MD direction (b).

[0039] FIG. 4 is a cross-sectional SEM image of the polyglycolic acid resin composition film of Comparative Example 4 (a) and the polyglycolic acid resin composition co-film of Example 3 (b).

[0040] Figure 5 The graphs are as follows: The tensile strength of the polyglycolic acid resin composition films prepared in Examples 2 and 4 and Comparative Examples 1, 2 and 4 varies with aging time, with the abscissa representing aging time (h) and the ordinate representing tensile strength (MPa).

[0041] Figure 6 The curves of elongation at break of the polyglycolic acid resin composition films prepared in Examples 2 and 4 and Comparative Examples 1, 2 and 4 versus aging time are shown in FIG. 1, wherein the abscissa represents aging time (h) and the ordinate represents elongation at break (%). DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0043] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0044] Source of raw materials

[0045] The raw materials used in the examples and comparative examples are all commercially available.

[0046] Polyglycolic acid (PGA), produced by Corbion Purac, has an intrinsic viscosity of 1.0-1.4 dl / g, a melting range of 200-230°C, and a melt flow rate of 46 g / 10 min at 230°C and 2.16 kg;

[0047] Polybutylene adipate terephthalate (PBAT), BASF C1200FBlend, melt index at 190°C, 2.16kg is 5.5g / 10min;

[0048] Chain extender, brand ADR-4370, produced by BASF, Germany;

[0049] Antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, triphenyl phosphite, Nanjing Jingtianwei Chemical Company.

[0050] The present invention performs performance measurement according to the following method:

[0051] Gel Permeation Chromatography (GPC): The test instrument was PL-GPC50 gel permeation chromatograph from Angilent, USA, and the processing software was GPCoffline. During the test, the mobile phase was hexafluoroisopropanol containing 5mmol / L sodium trifluoroacetate, the flow rate was 1mL / min, the column temperature was 40℃, the injection volume was 100μL, the standard sample was PMMA, and the sample concentration was 1mg / mL.

[0052] Melt flow rate (MFR) test: According to ISO1133 standard, LloydDavenport MFI-10 / 230 melt flow rate tester is used for measurement, barrel temperature is 230°C, weight load is 2.16kg, die diameter is 2.095mm, length is 8mm, preheating time is 4min, automatic sample cutting is performed at set time intervals, and the average value is calculated for 5 times. The measurement result is expressed in grams per 10 minutes (g / 10min).

[0053] Heat seal strength test: According to OB / T2358-1998 standard, INSTRON's 3344 film product testing machine was used for measurement, and the processing software was Bluehill 2.31 version. The film was cut into Type 2 in the ISO527-2 standard and placed in the Bluepard BPS-100CB constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) of Shanghai Yiheng Scientific Instrument Co., Ltd. for 24 hours. During the test, the initial clamp spacing was 50mm, and the test tensile rate was 300mm / min. With the heat seal as the center, peel off the upper film to the same position, open it 180°, clamp the two sections of the sample on the two clamps of the testing machine, and the lower end of the sample extends the same length. Each sample was tested 5 times and the average value was taken. Read the maximum load when the sample breaks.

[0054] Thermogravimetric analysis (TGA) test: The test was conducted on the Discovery series thermogravimetric analyzer of THERMALANALYSIS, and the processing software was TAInstrumentsTrios3.1.4. Before the test, the machine was preheated until the temperature of the balance cavity was stable at 40°C. During the test, 5-10 mg of sample was weighed and placed in a ceramic crucible, and the test was carried out in an air atmosphere with a flow rate of 20 mL / min. The temperature rise range was 30-600°C, and the heating rate was 10°C / min. The weight loss curve of the sample was recorded.

[0055] Film tensile test: According to ISO527-3 standard, the 3344 universal testing machine of INSTRON was used for measurement, and the processing software was Bluehill 2.31 version. The sample was cut into Type 5 in ISO527-3 standard and placed in the Bluepard BPS-100CB constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) of Shanghai Yiheng Scientific Instrument Co., Ltd. for 24 hours. During the test, the initial clamp spacing was 50mm, the test tensile rate was 500mm / min, each sample was tested 5 times, and the average value was taken.

[0056] SEM test: German Zeiss Merlin field emission scanning microscope was used for the test. First, the polyglycolic acid resin composite material sample was fractured with liquid nitrogen, and then the surface was sprayed with gold to observe the microscopic morphology of the sample cross section and the size of different dispersed phases.

[0057] Accelerated aging test: In the UV accelerated aging test, the sample film was placed in a xenon test chamber (Q-SUN Xe-3). The test sample was placed in a cavity fixed to an aluminum bracket. The device was exposed to an irradiance of 0.51W / m at a wavelength of 340nm. 2 The temperature was set at 38°C and the humidity was maintained at 50%.

[0058] [Comparative Example 1]

[0059] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. The moisture content of the polyglycolic acid particles after drying was 50 ppm. 25 parts of polyglycolic acid (PGA, Corbion Purac) and 75 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 20mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 4g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0060] [Comparative Example 2]

[0061] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. The moisture content of the polyglycolic acid particles after drying was 50 ppm. 30 parts of polyglycolic acid (PGA, Corbion Purac) and 70 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 20mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 2.5g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0062] [Comparative Example 3]

[0063] Preparation of polyglycolic acid grafted particles A:

[0064] Polyglycolic acid, butyl methacrylate, cumene hydroperoxide and antioxidant 1010 were fully premixed in a mass ratio of 400:12:0.6:0.8, and grafted using a co-rotating twin-screw extruder from Swedish Labtech. The speed was 200 rpm, and the extrusion temperatures were 190°C, 220°C, 230°C, 240°C, 240°C, 240°C, 240°C, 230°C and 225°C. The extruder was equipped with a circular die with a diameter of 3 mm. The strips were extruded from the die and air-cooled, and then cut into cylindrical yellow particles with a length of about 3 mm using a pelletizer, namely polyglycolic acid graft copolymer particles A. The melt flow rate was measured to be 98.9 g / 10 min, and the weight average molecular weight (M w ) was 119482 g / mol, and the polydispersity index (PDI) was 1.7. The particles were collected and packaged for later use.

[0065] [Comparative Example 4]

[0066] Preparation of polyglycolic acid resin composition:

[0067] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours and a water content of 50 ppm. 20 parts of polyglycolic acid (PGA, Corbion Purac), 5 parts of modified particles A, and 75 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 5.3g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0068] [Example 1]

[0069] Preparation of polyglycolic acid graft copolymer:

[0070] Polyglycolic acid, isobornene acrylate (brand: ARK, 95% stabilized with MEHQ), cumene hydroperoxide and antioxidant 1010 were fully premixed in a mass ratio of 400:12:0.6:0.8, and grafted using a co-rotating twin-screw extruder from Swedish Labtech. The speed was 200 rpm, and the extrusion temperatures were 190°C, 220°C, 230°C, 240°C, 240°C, 240°C, 240°C, 230°C and 225°C. The extruder was equipped with a circular die with a diameter of 3 mm. After the strip was extruded from the die and air-cooled, it was cut into cylindrical yellow particles with a length of about 3 mm by a pelletizer, i.e., polyglycolic acid graft copolymer particles B. The melt flow rate was measured to be 26.4 g / 10 min. The particles were collected and packaged for later use. The molecular weight of the graft copolymer was measured by GPC, with a weight average molecular weight (Mw) of 127892 g / mol and a polydispersity index (PDI) of 1.74.

[0071] [Example 2]

[0072] Preparation of polyglycolic acid resin composition:

[0073] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours and a water content of 50 ppm. 20 parts of polyglycolic acid (PGA, Corbion Purac), 5 parts of polyglycolic acid graft copolymer particles B, and 75 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 6.4g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0074] [Example 3]

[0075] Preparation of polyglycolic acid graft copolymer:

[0076] Polyglycolic acid, isobornene acrylate (brand: ARK, 95% stabilized with MEHQ), cumene hydroperoxide and antioxidant 1010 were fully premixed in a mass ratio of 800:18:0.8:1.6, and the grafting reaction was carried out using a co-rotating twin-screw extruder from Swedish Labtech. The rotation speed was 100 rpm, and the extrusion temperatures were 190°C, 220°C, 230°C, 240°C, 240°C, 240°C, 240°C, 230°C and 225°C. The extruder was equipped with a circular die with a diameter of 3 mm. After the specimen was extruded from the die and air-cooled, it was cut into cylindrical yellow particles with a length of about 3 mm by a pelletizer, namely polyglycolic acid graft copolymer particles C. The melt flow rate was measured to be 31.3 g / 10 min. The particles were collected and packaged for use. The molecular weight of the graft copolymer was measured by GPC, and the weight average molecular weight (M w ): 132175 g / mol, polydispersity index (PDI): 1.55.

[0077] [Example 4]

[0078] Preparation of polyglycolic acid resin composition:

[0079] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours and a water content of 50 ppm. 25 parts of polyglycolic acid (PGA, Corbion Purac), 5 parts of polyglycolic acid graft copolymer particles C, and 70 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 2.5g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0080] [Example 5]

[0081] Preparation of polyglycolic acid resin composition:

[0082] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a drying temperature of 35±2°C for 1 hour and a water content of 50 ppm. 30 parts of polyglycolic acid (PGA, Corbion Purac), 10 parts of polyglycolic acid graft copolymer particles C, and 60 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 4.8g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0083] [Example 6]

[0084] Preparation of polyglycolic acid resin composition:

[0085] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a drying temperature of 35±2°C for 2 hours and a water content of 50 ppm. 40 parts of fully dried polyglycolic acid (PGA, Corbion Purac), 10 parts of polyglycolic acid graft copolymer particles C, and 50 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts After being fully premixed, the ADR-4370 chain extender was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 6.1g / 10min. The particles were collected, vacuum dried in a 60℃ vacuum oven for 4h, and then packaged for use.

[0086] [Example 7]

[0087] Preparation of polyglycolic acid resin composition film:

[0088] The particles of Examples 1, 3 and Comparative Examples 1, 2, and 4 were fully dried and then heated in HAAKE TM The blown film was prepared on a RheomexOS single screw extruder with a screw diameter of 19 mm, an aspect ratio of 25, and a 3:1 standard metering screw. The single extruder was manufactured by HAAKE TM PolyLab TM OS torque rheometer platform control. The extruder has four heating sections, numbered 1-4 from the feed port to the outlet, and is equipped with a blown film die with a heating function, a die diameter of 19.5mm, a die gap of 0.5mm, a screw speed of 50rpm, and the temperatures of each section are set to 200℃, 210℃, 220℃ and 220℃, and then the film is made by cooling, shaping, drawing and winding. The thickness is controlled at about 25μm.

[0089] The particles of Examples 5 and 6 were fully dried and then placed in HAAKE TM The cast film was prepared on a RheomexOS single screw extruder with a screw diameter of 19 mm, an aspect ratio of 25, and a 3:1 standard metering screw. The single extruder was manufactured by HAAKE TM PolyLab TM The OS torque rheometer platform controls the screw speed to 30 rpm, and the temperatures of each section are set to 200°C, 210°C, 220°C and 220°C, and then the film is made by cooling, shaping, stretching and winding. The thickness is controlled to be around 20-30 μm.

[0090] [Example 8]

[0091] Preparation of injection-molded specimens of polyglycolic acid resin composition:

[0092] The particles of Example 1 and Comparative Examples 1 and 3 were fully dried and then heated in a HAAKE TM The processing was carried out on a MiniJet II micro injection molding machine. The mold was a 557-2295-60×10×1 mold produced by ThermoFisher Technology Company. During the experiment, the cavity temperature and mold temperature were set to 230°C and 60°C, respectively. During the injection molding process, the pressure was set to 300 bar for 5 seconds, and the subsequent holding pressure process was 100 bar for 20 seconds, after which the mold was demolded and the injection molded specimens were collected.

[0093] [Test Example 1]

[0094] The PGA raw material, five kinds of polyglycolic acid resin composition particles prepared in Examples 2, 4 and Comparative Examples 1, 2, and 4 were subjected to thermogravimetric analysis (TGA) and GPC tests according to the above-mentioned steps. The thermal decomposition temperature T d (5%) The specific values ​​are listed in Table 1.

[0095] Table 1. 5% thermal weight loss temperature of polyglycolic acid resin composition particles obtained in Examples and Comparative Examples

[0096] Sample PGA Raw Materials Comparative Example 1 Comparative Example 2 Comparative Example 4 Example 1 Example 4 <![CDATA[T d (5%) / ℃]]> 302 339.3 340 346.5 353.5 344

[0097] As can be seen from Figure 1 and Table 1, the addition of a polyglycolic acid graft copolymer with an unsaturated acrylic acid side chain containing a cyclic structure in Example 1 can significantly improve the thermal stability of the PGA blend. Compared with the 30% content of the polyglycolic acid graft copolymer without addition (Comparative Example 1), the TGA (5%) of Example 1 increased to 354°C, an increase of 15°C. This will be more conducive to the thermal processing of the PGA blend. At the same addition amount, the polyglycolic acid graft copolymer with acrylic acid side chains of other structures (Comparative Example 4) only increased the TGA (5%) of the PGA blend by 7°C. Compared with Comparative Example 2 (30 / 70PGA / PBAT blend), after adding 5% of the polyglycolic acid graft copolymer with an unsaturated acrylic acid side chain with a cyclic structure, the TGA (5%) of Example 4 increased by 4°C.

[0098] [Test Example 2]

[0099] The polyglycolic acid resin composite films and injection molded specimens prepared in Example 7 and Example 8 were quenched in liquid nitrogen, respectively, and then the cross sections were sprayed with gold and placed on a German ZEISSMERLIN scanning electron microscope (SEM) for observation. The obtained cross-sectional microstructures are shown in Figures 1-4.

[0100] It is obvious from Figure 1 (a), Figure 2 (a) and Figure 3 (a) that in the PGA / PBAT blend particles, PGA is dispersed in the PBAT continuous phase in a spherical structure. The average diameter of the polyglycolic acid (PGA) dispersed phase in the microstructure observed by scanning electron microscopy in Figure 1 (a) is about 300nm, and the average diameter of the PGA dispersed phase in Figure 2 (a) is 300-400nm. Compared with Comparative Examples 1 and 2, the PGA dispersed phase structure size in the blend particles prepared in Example 1 of Figure 3 (a) is significantly reduced, and the average diameter is about 200nm, indicating that the compatibility of PGA and PBAT of this composition is the best. At the same time, it can be seen from Figures 1 (b), 2 (b) and 3 (b) that due to the orientation during the processing process, PGA is distributed in the matrix in a rod shape after film blowing. Compared with Figure 1(b) and Figure 2(b), the PGA dispersed phase in the blend film prepared in Example 2 in Figure 3(b) is more obviously oriented in the rod-like structure along the processing direction, which confirms from the side that the interfacial force between PGA and PBAT matrix in Example 1 is stronger. Similarly, for the blend film with 30% PGA content, when no polyglycolic acid graft copolymer is added, it shows obvious brittle fracture ( Figure 4a ), PGA is distributed in a spherical shape and is relatively uneven. However, after adding polyglycolic acid graft copolymer in Example 4, the blend film shows obvious toughness fracture at the same content ( Figure 4b ), the PGA dispersed phase is mostly distributed in the continuous phase in the form of long strips, indicating that the graft copolymer has a compatibilizing effect.

[0101] [Test Example 3]

[0102] The five films in Example 7 were subjected to the xenon lamp accelerated aging equipment described above to evaluate the changes in the tensile strength and elongation at break of the films at different aging times. The results are as follows: Figure 5 and Figure 6 shown.

[0103] Compared with the film without adding polyglycolic acid graft copolymer (Comparative Example 1), after adding polyglycolic acid graft copolymer, due to the enhanced interface effect between PGA and PBAT in the blended composition, the tensile strength and elongation at break of the films of Comparative Example 4 and Example 2 are significantly improved compared with the film of the composition of Comparative Example 1. As the aging time increases, the tensile strength and elongation at break of the PGA / PBAT composition film are significantly reduced. Compared with the films of the compositions of Comparative Examples 2 and 4, the film of the composition of Example 2 still has higher tensile strength and elongation at break during the aging process. After 96 days of accelerated aging, the tensile strength of Example 2 is 23MPa, and the tensile strength retention rate is as high as 58%; the elongation at break is 246%, and the elongation at break retention rate is as high as 43%. This is mainly due to the special large sterically hindered non-polar side groups of the side chains of the modified PGA graft copolymer, which protect the PGA ester bond and give it better aging resistance. Although the modified PGA graft copolymer is also added to the composition of Comparative Example 3, its side chain groups do not have the characteristics of protecting the PGA ester bond, so its accelerated aging performance is worse than that of Example 2.

[0104] [Test Example 4]

[0105] The heat seal strength of the seven PGA / PBAT blend films prepared in Example 7 was measured according to the steps described above. The test results are listed in Table 2.

[0106] Table 2. Heat seal strength of comparative and example films

[0107] Sample Compatibilizer PGA content / % Heat seal strength / N Comparative Example 1 none 25 6.25 Comparative Example 2 none 30 5.4 Comparative Example 4 Polyglycolic acid graft copolymer particles A 25 3.91 Example 2 Polyglycolic acid graft copolymer particles B 25 10.59 Example 4 Polyglycolic acid graft copolymer particles C 30 10.9 Example 5 Polyglycolic acid graft copolymer particles C 40 10.8 Example 6 Polyglycolic acid graft copolymer particles C 50 11.1

[0108] Note: PGA content refers to the total amount of PGA contained in polyglycolic acid and polyglycolic acid graft copolymer in the film material.

[0109] For packaging film applications, the heat seal strength of the composite film is directly related to whether it can be actually applied or the quality of the application. From the results in Table 2, it can be seen that the heat seal strength of the film in Comparative Example 1 (20 / 80PGA / PBAT composite film) is only 6.25N. After adding the modified particles A of polyglycolic acid / butyl methacrylate graft copolymer to Comparative Example 4, the heat seal performance of the film in Comparative Example 3 is reduced. After adding the polyglycolic acid graft copolymer with a cyclic structure-like side group (modified particles B) to Example 2, the heat seal strength is significantly improved (69%). Similarly, after adding the polyglycolic acid graft copolymer with a cyclic structure-like side group (particle C) to Example 4, the heat seal strength is significantly improved (102%) compared to Comparative Example 2, indicating that the present invention adds a polyglycolic acid graft copolymer with a specific structure to the polyglycolic acid resin composition, which exhibits more excellent aging stability.

Claims

1. A polyglycolic acid resin composition comprising: Polyglycolic acid, polyglycolic acid graft copolymer, mixture of aliphatic dibasic acid-aromatic dibasic acid-diol copolyester and / or reaction products thereof, wherein the structural unit with side chain in the polyglycolic acid graft copolymer is a derivative of a monomer compound containing at least one α, β-unsaturated group.

2. The polyglycolic acid resin composition according to claim 1, characterized in that The monomer compound containing at least one α,β-unsaturated group is selected from at least one of acrylic unsaturated monomers containing a cyclic structure, preferably at least one of cyclohexyl methacrylate, dicyclopentyl methacrylate, isobornene acrylate, benzyl acrylate, benzyl methacrylate, and glycidyl acrylate; and / or, In the polyglycolic acid graft copolymer, the main chain structure accounts for 80-99% of the total mass of the copolymer, and the side chain structure accounts for 1-20% of the total mass of the copolymer; preferably, in the polyglycolic acid graft copolymer, the main chain structure accounts for 95-99% of the total mass of the copolymer, and the side chain structure accounts for 1-5% of the total mass of the copolymer; and / or, The weight average molecular weight of the polyglycolic acid graft copolymer is 80,000 to 300,000 g / mol, preferably 110,000 to 160,000 g / mol; and / or, The intrinsic viscosity of the polyglycolic acid is 0.9 to 7 dl / g, preferably 1 to 5 dl / g; and / or, The polyglycolic acid has a melt flow rate of 1 to 90 g / 10 min, preferably 1 to 50 g / 10 min, measured at 230° C. and 2.16 kg; and / or The aliphatic dibasic acid-aromatic dibasic acid-diol copolyester is selected from at least one of polybutylene adipate terephthalate and polybutylene succinate terephthalate.

3. The polyglycolic acid resin composition according to claim 1, characterized in that Taking the total mass of the polyglycolic acid, the polyglycolic acid graft copolymer and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the polyglycolic acid accounts for 10-70%, the polyglycolic acid graft copolymer accounts for 1-20%, and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester accounts for 10-89%; preferably, taking the total mass of the polyglycolic acid, the polyglycolic acid graft copolymer and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the polyglycolic acid accounts for 20-60%, the polyglycolic acid graft copolymer accounts for 1-10%, and the aliphatic dibasic acid-aromatic dibasic acid-diol copolyester accounts for 30-79%.

4. The polyglycolic acid resin composition according to claim 1, characterized in that The polyglycolic acid resin composition further comprises a functional additive, and preferably, the functional additive is selected from at least one of an antioxidant A, a chain extender, and an opening agent.

5. The polyglycolic acid resin composition according to claim 4, characterized in that: The antioxidant A is selected from at least one of hindered phenols, hindered amines, phosphites and thiols; and / or, The chain extender is selected from at least one of multifunctional compounds or grafts containing multiple epoxy groups or isocyanate groups, preferably at least one of diphenylmethane diisocyanate, dioxazoline, glycidyl methacrylate, and styrene-methyl methacrylate-maleic anhydride copolymer; and / or, The opening agent is selected from fatty acid amide compounds, preferably at least one of oleamide, erucamide and stearamide; and / or, Based on the total mass of the polyglycolic acid, polyglycolic acid graft copolymer and aliphatic dibasic acid-aromatic dibasic acid-diol copolyester as 100%, the functional additive is 0.1-15%, preferably 0.5-10%.

6. The polyglycolic acid resin composition according to any one of claims 1 to 5, characterized in that The thermal decomposition temperature T of the polyglycolic acid resin composition for 5% weight loss d >340°C, the average diameter of the dispersed phase of polyglycolic acid in the microstructure observed by scanning electron microscopy is <400nm.

7. A method for preparing the polyglycolic acid resin composition according to any one of claims 1 to 6, comprising: The components including the polyglycolic acid, aliphatic dibasic acid-aromatic dibasic acid-diol copolyester and polyglycolic acid graft copolymer are fully mixed, and then melt-blended and extruded to obtain the polyglycolic acid resin composition.

8. The preparation method according to claim 7, characterized in that: The polyglycolic acid, aliphatic dibasic acid-aromatic dibasic acid-diol copolyester and polyglycolic acid graft copolymer are dried before mixing, preferably at a drying temperature of 10 to 80° C., preferably 10 to 40° C.; and / or, The conditions for melt blending and extrusion are: the temperature of melt blending and extrusion is 180-260° C., and the speed of the extruder is 10-500 rpm; preferably, the temperature of melt blending and extrusion is 190-250° C., and the speed of the extruder is 100-250 rpm; and / or, Functional additives are also added during the mixing process.

9. The preparation method according to claim 7, characterized in that: The polyglycolic acid graft copolymer is obtained by mixing polyglycolic acid and an acrylic unsaturated monomer containing a cyclic structure, and then subjecting the mixture to a grafting reaction under the action of an initiator. The grafting reaction is preferably carried out using a screw extruder, and more preferably, the screw extruder is a twin-screw extruder.

10. The preparation method according to claim 9, characterized in that: The initiator is selected from organic peroxide initiators, preferably at least one selected from cumene hydroperoxide, tert-butylbenzene peroxide, dibenzoyl peroxide, and dicumyl peroxide; and / or, Based on the total mass of the polyglycolic acid and the acrylic unsaturated monomer containing a cyclic structure as 100%, the acrylic unsaturated monomer is 0.1 to 5%, preferably 1 to 3%; and / or, Based on the total mass of the polyglycolic acid and the acrylic unsaturated monomer containing a cyclic structure as 100%, the initiator is 0.01 to 1%, preferably 0.05 to 0.3%; and / or, The temperature of the grafting reaction is 170 to 250° C., preferably 180 to 240° C.; and / or, Antioxidant B is optionally added during the mixing process.

11. The preparation method according to claim 10, characterized in that: The antioxidant B is selected from at least one of hindered phenols, hindered amines, phosphites and thiols; and / or, Based on the total mass of the polyglycolic acid and the acrylic unsaturated monomer containing a cyclic structure being 100%, the antioxidant B is 0.1-5%.

12. Use of the polyglycolic acid resin composition according to any one of claims 1 to 6 or the polyglycolic acid resin composition obtained by the preparation method according to any one of claims 7 to 11 in the preparation of blown films, cast films, injection molded parts and sheets.

13. The use according to claim 12, characterized in that: The heat sealing strength of the polyglycolic acid resin composition film is greater than 8N, and the retention rate of the elongation at break after xenon lamp aging for 100 hours is greater than or equal to 16%.

Citation Information

Patent Citations

  • Modified polyglycolic acid biodegradable mulch film and preparation method thereof

    CN109575536A

  • Polyglycolic acid composition as well as preparation method and application thereof

    CN114075378A